Penyusunan Skala Perilaku Anti Korupsi - Erina Resti Handayani; Adi Heryadi (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2025)
The purpose of this study is to measure anti-corruption behavior in employees or active workers and to develop anti-corruption behavior measurement instruments so that studies on anti-corruption behavior can be developed more broadly. This study uses quantitative methods, data collected by questionnaire scale technique. The research subjects amounted to 30 active workers. The data analysis technique used is validity test and reliability test with alpha-cronbach approach. The results of the research on anti-corruption behavior scale research consisting of 21 items have a reliability value of 0.850. This shows that the scale prepared is considered well worth using as an instrument to measure anti- corruption behavior.